Análisis del Impacto del Fenómeno Covid-19 en las Empresas Turísticas en San Agustín Huila (2021)
Tourism has been one of the sectors most affected globally by the crisis unleashed by the Covid19 pandemic, and constitutes one of the most important productive bets in the department of Huila. In this monograph, an analysis of the impact of the Covid19 phenomenon on tourism companies in the municipality of San Agustín is carried out, through consultation with acto rs linked to the sector, such as tourism service providers and establishments with activities related to the sightseeing. In this way, information was collected that made it possible to measure in figures the level of impact of the sector and the social and economic repercussions in the municipality. The research is developed from the quantitative approach, and being a first approach to the subject, it is also framed within the exploratory research method.